Comparative Evidence on the 0.5% Final Tax Rate and Tax Sanctions for Indonesian MSME Compliance: A Systematic Review - Andri Krisandy; Sekar Mayangsari (Summa : Journal of Accounting and Tax, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy; however, their contribution to tax revenue remains relatively limited, creating an ongoing challenge for policymakers to improve compliance while supporting business sustainability. This study reviews and synthesizes evidence from prior empirical studies on the association between the 0.5% final tax rate and tax sanctions and MSME taxpayer compliance in Indonesia. Using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines, 569 records were initially identified from Scopus, Google Scholar, ProQuest, and SINTA. Following screening and eligibility assessment, 31 studies published between 2018 and 2026 were included in the review. The analysis was conducted using a thematic comparative synthesis, examining the direction of findings, consistency of relationships, and frequency of statistical significance reported across the selected studies. The results indicate that both the 0.5% final tax rate and tax sanctions are generally associated with higher MSME taxpayer compliance. Based on the synthesis of evidence across studies, findings related to tax sanctions appear more consistent and more frequently reported as statistically significant, whereas findings on the tax rate are comparatively mixed and context-dependent. These conclusions should be interpreted within the scope and limitations of the reviewed literature, including variations in research design, sample characteristics, and measurement approaches across studies. Overall, the review suggests that enforcement mechanisms may play an important role, while preferential tax rates may serve as a complementary policy instrument in improving MSME tax compliance in Indonesia.